Griscelli syndrome and periodontal therapy approach: A case report - Mamakoğlu, Dilek; Kuru Leyla (My University, 2013)
Griscelli Syndrome (GS), a rare autosomal recessive genetic disorder characterized with pigmentary dilution of the skin, malfunctions of humoral and cellular immunity, was first described by Claude Griscelli in 1978. In this report, periodontal therapy and follow-up of a 10 year-old girl with GS type 2, who applied to our clinic with complaints of gingival bleeding and redness, was presented. The patient had silvery-grey coloured hair and eyebrow, well-rounded nose radix and tip, and hemiparesthesia at the right part of her body. Intraoral examination revealed pigmentation of the lips, heavy accumulation of microbial dental plaque, hyperemia and edema at gingiva. She was diagnosed with plaque-induced gingivitis, and initial periodontal treatment including oral hygiene instructions, scaling and polishing was performed under recommended antibiotic prophylaxis. She was followed up with 1 month intervals. After 6 months, she attended to the clinic with clinical signs of acute necrotizing ulcerative gingivitis and was treated with diluted hydrogen peroxide and chlorhexidine digluconate (0.2%) rinse. Due to the hyperactivity of T lymphocytes and macrophages, intensive host response to dental plaque in patients with GS can be seen. In conclusion, importance of oral hygiene should be emphasized in establishing high level of oral health and, maintenance of patients with GS should be carried out with short intervals.
Keywords: Griscelli syndrome type 2; nonsurgical periodontal debridement; acute necrotizing ulcerative gingivitis